2022
DOI: 10.48550/arxiv.2203.07809
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Image Quality Assessment for Magnetic Resonance Imaging

Abstract: Image quality assessment (IQA) algorithms aim to reproduce the human's perception of the image quality. The growing popularity of image enhancement, generation, and recovery models instigated the development of many methods to assess their performance. However, most IQA solutions are designed to predict image quality in the general domain, with the applicability to specific areas, such as medical imaging, remaining questionable. Moreover, the selection of these IQA metrics for a specific task typically involve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…Previous studies [36,9] showed non-linear relation between IQM scores and human accessors' scores. A common solution is to apply a non-linear regression by adopting the five-parameter modified logistic function [40].…”
Section: Evaluation Criteriamentioning
confidence: 85%
See 4 more Smart Citations
“…Previous studies [36,9] showed non-linear relation between IQM scores and human accessors' scores. A common solution is to apply a non-linear regression by adopting the five-parameter modified logistic function [40].…”
Section: Evaluation Criteriamentioning
confidence: 85%
“…Previous studies of IQMs showed their efficiency in reflecting the human perception of visual quality [35,36,37,9]. That brings a temptation to use the best-performing differentiable IQMs as the loss functions for a direct optimization of the image processing models [38].…”
Section: Metrics As Loss Functionsmentioning
confidence: 99%
See 3 more Smart Citations